2022
DOI: 10.1249/01.mss.0000876668.76718.ba
|View full text |Cite
|
Sign up to set email alerts
|

Applying Theory Of Planned Behavior To Examine Adolescent Female Athletes’ Intentions Of Continued Sport Participation

Abstract: RESULTS: Players were 20.1 ± 1.1 years of age. Across all practice and competition sessions, the mean duration of exercise was 59.0 ± 38.8 min, total distance covered was 2,518.9 ± 2,074.5 m, and estimated energy consumption was 381.7 ± 284.8 kcals. Athletes performed 5.9 ± 7.9 sprints per session, maintained an average speed of 2.8 ± 1.2 km/h, and achieved a maximum speed of 20.7 ± 7.3 km/h. Average HR was 131.9 ± 24.3 bpm, maximum HR was 177.4 ± 32.7 bpm, training load was 70.1 ± 59.3, and cardio load was 76… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Jeng et al’s study demonstrated that attitudes, subjective norms, and perceived behavioral control all influence older adults’ intentions to continue in virtual reality leisure activities [ 15 ]. Hopkins et al used the TPB to examine the intentions of adolescent female athletes to continue participating in sports, and the results indicated that these three variables were similarly validated for their effects on intentions to continue participating in sports [ 16 ]. All of the above studies verified that the independent variables in the TPB are the influencing factors that affect users’ continued participation in sports and that the purpose of users’ use of online sports videos is to engage in sports, so we can speculate that there is appropriateness in utilizing the variables in the TPB model to explain the factors that affect the decision to continue using online sports videos.…”
Section: Introductionmentioning
confidence: 99%
“…Jeng et al’s study demonstrated that attitudes, subjective norms, and perceived behavioral control all influence older adults’ intentions to continue in virtual reality leisure activities [ 15 ]. Hopkins et al used the TPB to examine the intentions of adolescent female athletes to continue participating in sports, and the results indicated that these three variables were similarly validated for their effects on intentions to continue participating in sports [ 16 ]. All of the above studies verified that the independent variables in the TPB are the influencing factors that affect users’ continued participation in sports and that the purpose of users’ use of online sports videos is to engage in sports, so we can speculate that there is appropriateness in utilizing the variables in the TPB model to explain the factors that affect the decision to continue using online sports videos.…”
Section: Introductionmentioning
confidence: 99%